Keanekaragaman, komposisi spesies, dan kunci identifikasi lalat buah (Diptera: Tephritidae: Dacinae) di Pulau Lombok - Syarron Hudiwaku; Toto Himawan; Akhmad Rizali (Jurnal Entomologi Indonesia, 2022)
Information about fruit flies (Diptera: Tephritidae: Dacinae) diversity in Lombok island is still lacking. This study was aimed to determine the diversity and species composition of the Dacinae fruit flies as well as developed the identification key of fruit flies in Lombok island. The research was conducted in 6 locations i.e., Nature Park (NP) of Kerandangan, NP of Suranadi, Lemor forest, Gangga garden, Lingsar garden, dan Lemor garden, spread across the island of Lombok from March to June 2020. Each location consisted of 6 observation plots using the transect method as far as one kilometer with a distance between the plots of 200 m. Fruit flies were collected using a steiner type trap with different attractants i.e. namely methyl eugenol (ME) and cue lure (CL). Identification of fruit flies were carried out at the Plant Quarantine Laboratory, Balai Karantina Pertanian Kelas I Mataram. Overall 22 species from 210,267 individuals of fruit flies were collected with 4 dominance species were Bactrocera limbifera, B. caudata, B. carambolae, and B. dorsalis. The most abundant spesies was B. carambolae which comprises 47% of the total population. Based on 22 species that recorded in this research, the identification key of fruit flies in Lombok Island was constructed. A dichotomous key is provided that describes 2 genera, 4 subgenus, and 22 species of fruit flies. The identification key uses a morphological character matrix, by comparing several key morphological characters in determining species of fruit flies.